Democratic and expert legitimacy: Science, politics and the public during the COVID-19 pandemic. (11th February 2022) - Weingart, Peter; van Schalkwyk, François; Guenther, Lars
Abstract: The COVID-19 pandemic has provided an extraordinary test case for an analysis of the interrelations between policymakers and scientific experts faced with grave decisions and given the respective levels of trust they enjoy. The article provides a comparative analysis between three countries—Germany, the USA and South Africa (SA)—of the interrelation between the public's perceptions of the threat posed by the pandemic, the trust in governments and in scientific experts formally organized to advise governments, and the acceptance of governments' decisions to mitigate the pandemic. These scientific experts enjoyed a high degree of acceptance even when admitting uncertainty and the need for further research. Support for politicians also remained high in spite of the severity of the measures implemented and their increasingly evident departure from their experts' advice. However, trust in politicians deteriorated as the pandemic progressed, most dramatically in the USA, less so in SA and Germany, due to the politicization of the pandemic. The analysis is limited to events during 2020.